THE USE OF MODERN TECHNOLOGY IN THE TRANSLATION OF ADVERTISEMENTS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In today’s globalized market, advertising plays a critical role in reaching diverse international audiences. Accurate and culturally appropriate translation of advertisements is essential for maintaining brand identity and maximizing consumer impact across different regions. This paper explores how modern technologies — including neural machine translation (NMT), computer-assisted translation (CAT) tools, artificial intelligence (AI), and localization software — are transforming the field of advertising translation. Drawing from recent studies and practical applications, the paper highlights both the advantages and limitations of using technology in this context. While these tools offer speed, consistency, and cost-efficiency, challenges remain in preserving cultural nuances, emotional tone, and persuasive language. The paper also emphasizes the growing importance of hybrid approaches, where human expertise complements machine output through techniques like transcreation. Ultimately, the research demonstrates that integrating modern technology with human creativity can significantly improve the quality and effectiveness of translated advertisements in global markets.